Hubungan Antara Kecemasan Akademik Dengan Konsentrasi Belajar Siswa Kelas X Di SMAN 10 Kota Bogor - Shopiya Maolidah; Putri Ria Angelina; Khaidir Fadil (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Adolescence is a period that is vulnerable to stress, including stress related to academic demands. Academic stress can cause pressure that triggers academic anxiety, a psychological condition that has the potential to disrupt students' concentration in learning. This concentration disorder can cause students to have difficulty in understanding learning materials. This study aims to determine the relationship between academic anxiety and the concentration of learning of class X students at SMAN 10 Bogor City. This study uses a quantitative approach with a correlational research method. Data collection techniques use questionnaires and observations. The data analysis techniques used are descriptive analysis, normality tests and correlation tests. The population used was 319 students with a sample of 216 students, and the sampling technique used was area sampling. The results of the study showed that there was a significant relationship between academic anxiety and learning concentration with a correlation coefficient value of -0.565 and a significance value of <0.001. This indicates a negative correlation, which means that the higher the academic anxiety, the lower the concentration of learning. Conversely, the lower the academic anxiety, the higher the concentration of learning. So, it can be concluded that academic anxiety has a relationship with learning concentration, and the relationship is a negative relationship.